Escola e meio ambiente : a educação das crianças brasileiras residentes no entorno do Parque Nacional Serra de Itabaiana - Santos, Leonice Santana Ferreira dos (2015)
ABSTRACT: This study has as the subject the environmental education in schools located around of the protected area called Parque Nacional Serra de Itabaiana (PARNASI), in the city of Itabaiana, state of Sergipe. Therefore, it was tried to analyze the way that the environmental dimension is worked in schools about the PARNASI. The research was performed with two schools of that area: Escola Municipal Dom José Thomaz and Escola Municipal Luiz Forest, located in the villages Rio das Pedras and Bom Jardim, respectively. The study consists of a qualitative research that focuses on the bibliographies sources related to the works of the main authors who discuss the topic of environmental education associated with protected areas in Brazil. The bibliographic research also shows the existing studies on the PARNASI in general. With documentary source research resort on the political-educational projects of the schools. Semi-structured interviews were conducted with managers of schools, teachers and parents of the students. The analytical process is guided by forms of qualitative textual analysis which start from the choice of categories focused on the description and understanding of the main subject. The research result shows that the subjects involved in the structure and operation of the investigating schools, it still have naturalistic conceptions of environment, recursistas, systemic, humanistic and biorregionalista. Respondents recognize the importance of working in schools EA also assumed you already developed some action in this regard. Thus, environmental education initiatives developed by schools located around the PARNASI are limited to the principles beautified by the National Environmental Education Policy (PNEA). It appears, this way the necessity of continuous education programs for teachers of schools investigated enable us to the work of environmental education proposed by the rules that governing the Brazilian public policies in this sector.